The evolution of sport psychiatry, Circa 2009 - Glick, I. D.; Kamm, R.; Morse, E. (Sports Medicine, 2009)
Over the past three decades, the world of both amateur and professional sports has expanded greatly and become more complex. In part related to these changes - and relatively unknown to sports medicine practitioners - the field of sport psychiatry has steadily evolved and grown. This paper focuses on what these changes have been.